2002
DOI: 10.1002/mus.10023
|View full text |Cite
|
Sign up to set email alerts
|

Running endurance abnormality in mdx mice

Abstract: The mdx mouse lacks dystrophin and has histological features of Duchenne muscular dystrophy but little weakness in the first year of life. We report here an early deficit in voluntary wheel running, as assayed with a computerized wheel. All mdx mice showed an intermittent running pattern, in contrast to the continuous running seen in controls. The average continuous running time differed significantly between mdx and control mice at all ages tested (5-21 weeks). This assay is noninvasive, has the advantage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…We therefore hypothesized that Type I diabetes not only reduces total spontaneous exercise but also fragments the temporal pattern of running, similar to that described in mdx dystrophic mice (9). Studies used an acquired Type I diabetes model (streptozotocin-induced diabetes) rather than a genetic diabetic model to make certain that diabetic and normal animals would not differ genetically in ways unrelated to diabetes that could affect spontaneous running behavior.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…We therefore hypothesized that Type I diabetes not only reduces total spontaneous exercise but also fragments the temporal pattern of running, similar to that described in mdx dystrophic mice (9). Studies used an acquired Type I diabetes model (streptozotocin-induced diabetes) rather than a genetic diabetic model to make certain that diabetic and normal animals would not differ genetically in ways unrelated to diabetes that could affect spontaneous running behavior.…”
mentioning
confidence: 96%
“…Mice with mdx muscular dystrophy have the analogous genotype as humans with Duchenne muscular dystrophy, although they have a milder phenotype, with muscle weakness being prominent in the diaphragm but minimal in the limbs. Studies of spontaneous wheel running in mdx mice have found not only reductions in total running distance (4,9) but also alterations in the temporal pattern of running. Specifically, mdx dystrophic mice demonstrate much more intermittent running than normal (a "stop and go" pattern), which is believed to be due to an abnormality in muscle endurance (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these observations, we thought that AQP4 may play the important roles in association with the force generation in skeletal myofibers. While Hara et al (2002) reported that the running endurance is decreased in AQP4 deficient mdx mice as compared with that of control mice. This might be due in part to the depleted expression of AQP4 in mdx mouse skeletal myofibers.…”
Section: Introductionmentioning
confidence: 92%
“…Interference with genes of the core circadian clock and with genes regulating narcolepsy can also result in major dysregulation of both the levels of activity and of their distribution across the circadian period (Vanitallie, 2006;Dibner et al, 2010). Other possible causes of changes in physical activity are structural abnormalities of bones or skeletal muscle (Hara et al, 2002;Connolly et al, 2003). Respiratory and cardiovascular parameters are also major determinants of activity, as defective supply of oxygen and nutrients to skeletal muscle can impair contraction.…”
Section: Spontaneousmentioning
confidence: 99%